Identification of genes controlling compatible and incompatible reactions of pearl millet (Pennisetum glaucum) against blast (Magnaporthe grisea) pathogen through RNA-Seq - Singh, Shweta; Sharma, Rajan; Nepolean, Thirunavukkarasu; Nayak, Spurthi N.; Pushpavathi, Bheemavarapu; Khan, Aamir W.; Srivastava, Rakesh K.; Varshney, Rajeev K. (Frontiers in Plant Science, 2022)
Blast [Magnaporthe grisea (Herbert) Barr] is an economically important disease in Asian pearl millet production ecologies. The recurrent occurrence of blast in the past one decade has caused enormous strain on grain and forage production. Identification of resistance genes is an important step to develop durable varieties. The present study is the first attempt to use RNA-Seq to investigate the transcript dynamics in a pearl millet inbred ICMB 93333, which had a unique differential reaction to two isolates- Pg 45 (avirulent) and Pg 174 (virulent) of M. grisea. The inbred was inoculated by both isolates and samples taken at six different time intervals for genome-wide RNA-Seq experiment. The transcriptome results revealed the differential expression of more than 2300 genes. The time-specific comparison showed activation or repression of specific genes in various pathways. Genes and transcriptions factors related to pathogenesis-related proteins, reactive oxygen species generating and its scavenging genes, cell wall defense, primary and secondary metabolic pathways, and signaling pathways were identified by comparing the host-plant compatible and incompatible interactions. The genes identified from this experiment could be useful to understand the host-plant resistance and design novel strategies to manage blast disease in pearl millet.